PENYULUHAN LITERASI KEUANGAN GUNA MENUMBUHKAN KEBIASAAN MENABUNG SEJAK DINI DI SEKOLAH DASAR NEGERI 1 (SATU) BUGIS - Vina Agustina; Reva Rahayu; Imron Fathurohman; Septian Eka Prahardik; Zumara (Jurnal Istimā, 2025)
Low financial literacy among elementary school students affects their understanding of the value of money, financial management, and the importance of saving from an early age. This condition is evident among students at SDN 1 Bugis, where most children do not yet have an independent saving habit and tend to display consumptive behavior. This community service activity aims to enhance financial literacy and foster saving habits through interactive counseling sessions. The methods used include presentations, discussions, simple simulations on managing pocket money, and question–answer sessions. The activity was carried out on August 2, 2025, and involved all students from grades 1 to 6. The results indicate an improvement in students’ understanding of basic financial concepts, the benefits of saving, and the development of a more positive attitude toward financial management. The program also succeeded in encouraging students to regularly set aside their pocket money as an initial step toward building responsible financial behavior. Thus, this activity contributes to strengthening financial literacy from an early age through enjoyable and practical educational approaches.